Regenerating Immunotolerance in Multiple Sclerosis with Autologous Hematopoietic Stem Cell Transplant - Massey, Jennifer C.; Sutton, Ian J.; Ma, David D. F.; Moore, John J. (Frontiers in Immunology, 2018)
Multiple Sclerosis (MS) is an inflammatory disorder of the central nervous system where evidence implicates an aberrant adaptive immune response in the accrual of neurological disability. The inflammatory phase of the disease responds to immunomodulation to varying degrees of efficacy, however no therapy has been proven to arrest progression of disability. Recently, more intensive therapies, including immunoablation with autologous haematopoietic stem cell transplantation (AHSCT) have been offered as a treatment option to retard inflammatory disease, prior to patients becoming irreversibly disabled. Empirical clinical observations support the notion that the immune reconstitution that occurs following AHSCT is associated with a sustained therapeutic benefit, however neither the pathogenesis of MS nor the mechanism by which AHSCT results in a therapeutic benefit has been clearly delineated. Although the antigenic target of the aberrant immune response in MS is not defined, accumulated data suggest that immune reconstitution following AHSCT results in an immunotolerant state through deletion of pathogenic clones by a combination of direct ablation and induction of a lymphopenic state driving replicative senescence and clonal attrition. Restoration of immunoregulation is evidenced by changes in regulatory T cell populations following AHSCT and normalisation of genetic signatures of immune homeostasis. Furthermore, some evidence exists that AHSCT may induce a rebooting of thymic function and regeneration of a diversified naïve T cell repertoire equipped to appropriately modulate the immune system in response to future antigenic challenge. In this review, we discuss the immunological mechanisms of immune reconstitution therapies, focusing on AHSCT, as a means of recalibrating the dysfunctional immune response observed in MS.